What influences patients’ acceptance of a blood pressure telemonitoring service in primary care? A qualitative study - Abdullah, A.; Liew, S.M.; Hanafi, N.S.; Ng, C.J.; Lai, P.S.M.; Chia, Y.C.; Chu Kiong, L. (Dove Medical Press, 2016)
Background: Telemonitoring of home blood pressure (BP) is found to have a positive effect on BP control. Delivering a BP telemonitoring service in primary care offers primary care physicians an innovative approach toward management of their patients with hypertension. However, little is known about patients’ acceptance of such service in routine clinical care. Objective: This study aimed to explore patients’ acceptance of a BP telemonitoring service delivered in primary care based on the technology acceptance model (TAM). Methods: A qualitative study design was used. Primary care patients with uncontrolled office BP who fulfilled the inclusion criteria were enrolled into a BP telemonitoring service offered between the period August 2012 and September 2012. This service was delivered at an urban primary care clinic in Kuala Lumpur, Malaysia. Twenty patients used the BP telemonitoring service. Of these, 17 patients consented to share their views and experiences through five in-depth interviews and two focus group discussions. An interview guide was developed based on the TAM. The interviews were audio-recorded and transcribed verbatim. Thematic analysis was used for analysis. Results: Patients found the BP telemonitoring service easy to use but struggled with the perceived usefulness of doing so. They expressed confusion in making sense of the monitored home BP readings. They often thought about the implications of these readings to their hypertension management and overall health. Patients wanted more feedback from their doctors and suggested improvement to the BP telemonitoring functionalities to improve interactions. Patients cited being involved in research as the main reason for their intention to use the service. They felt that patients with limited experience with the internet and information technology, who worked out of town, or who had an outdoor hobby would not be able to benefit from such a service. Conclusion: Patients found BP telemonitoring service in primary care easy to use but needed help to interpret the meanings of monitored BP readings. Implementations of BP telemonitoring service must tackle these issues to maximize the patients’ acceptance of a BP telemonitoring service.